SenseWeb: Shared Macro-scopes for Scientific Exploration - Kansal, Aman; Nath, Suman; Zhao, Feng (Microsoft eScience Workshop at RENCI, 2007)
Many advances in science come from observing the previously unobserved. However, developing, deploying, and maintaining the instrumentation required to observe the phenomenon under investigation is a significant overhead for scientists. In most cases, scientists are restricted to collecting data using limited individual resources. As a first step to overcome this limitation, central archives for sharing data have emerged, so that data collected in individual experiments can be re-used by others. We take the next step in this direction: we build an infrastructure, SenseWeb, to enable sharing the sensing instrumentation itself among multiple teams. The key idea is as follows. A scientist deploys sensors to observe a phenomenon, say soil moisture, at their site. The sensors are shared over SenseWeb. Other scientists interested in soil moisture can conduct experiments using these sensors through SenseWeb. Further, other ecologists may deploy similar sensors at their sites and share them. The scientist can now use SenseWeb to access not only her own sensors but also these other similar ones. What emerges is a “macro-scope” of shared sensors measuring the phenomenon at a scale that no single scientist could instrument alone. New experiments are enabled, providing new insights by probing a phenomenon from multiple sites. Barrier to discovery is reduced as many experiments can begin without deployment overhead. SenseWeb addresses challenges in supporting highly heterogeneous sensors, each with their own capability, precision, or sharing willingness. It is built for scalability, allowing multiple concurrent experiments to access common resources. Its map based web interface provides data visualization. Our prototype is currently used by nearly a dozen research teams to share sensors observing different phenomenon ranging from coral ecosystems to urban activity.